Numerical analysis and optimal design to reduce residual stresses and deformations of die casting baseplate after ejection - Kim, Taesan; Jin, Kai; Kim, Naksoo; Kim, Byeonggon (Journal of mechanical science and technology, 2015)
During the manufacturing process of die casting baseplate, residual stresses and deformations, such as warping, local bending and shrinkage, are produced due to the changes of temperature, pressure and cooling regime during the packing and cooling stages. Using the Elastic-plastic model of AZ91D magnesium alloys at different temperature, a numerical analysis model for the die casting baseplate which combines with the influence of residual stresses generated at the packing and cooling stages was built. To verify the numerical results, 3D scanning technology was used that measured the deformation of the whole baseplate and drew a deformation pattern. Through comparison, it is concluded that the calculated deformations were consistent with that of measurement. Furthermore, the residual stresses were generated differently due to the process parameter change, so that the optimal design was taken for mold temperature, packing pressure and packing and cooling regime. Through optimal design, baseplate deformation was reduced effectively.